(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
Brugada syndrome is a disorder caused by alteration or mutation in the ion channels, abnormal ECG resulting in elevated ST segment and blockage of right bundle brank. It has a genetic history and can be passed down from the parents to their offspring and may be further complicated if someone already had a cardiac arrest or other cardiac-related issues. At present, there is no permanent cure strategy available to treat this disorder. However, some surgical and pharmacological intervention approaches, such as the use of defibrillators, catheters can provide some relief, but due to their excessive cost and complications, their use has been limited. Polyunsaturated fatty acids (PUFA) components: Eicosapentaenoic acid and docosahexaenoic acid were found to play a significant role in reducing the cardiovascular events and mortality rate. The primary sources of these fatty acids are fish and fish oils. This review attempts to summarize the cardioprotective role of PUFA in preventing ventricular arrhythmias and Brugada syndrome through alteration of cardiac ion channels.